2019
DOI: 10.3390/rs11161860
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Vegetation Variations and Main Drivers over the Agropastoral Ecotone of Northern China through the Ensemble Empirical Mode Decomposition Method

Abstract: Vegetation is the major component of the terrestrial ecosystem. Understanding both climate change and anthropogenically induced vegetation variation is essential for ecosystem management. In this study, we used an ensemble empirical mode decomposition (EEMD) method and a linear regression model to investigate spatiotemporal variations in the normalized difference vegetation index (NDVI) over the agropastoral ecotone of northern China (APENC) during the 1982–2015 period. A quantitative approach was proposed bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Specifically, we examined the changes in precipitation, ET, and moisture recycling in the APENC. We found that, over the period of 1995-2015, there were varying but increasing trends in the annual P in the APENC, a finding similar to previous studies (Xue et al 2019). Annual mean regional ET exhibited significant increasing trends from 1995 to 2015, indicating that the revegetation has enhanced regional ET, confirming the results of previous study (Wang et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, we examined the changes in precipitation, ET, and moisture recycling in the APENC. We found that, over the period of 1995-2015, there were varying but increasing trends in the annual P in the APENC, a finding similar to previous studies (Xue et al 2019). Annual mean regional ET exhibited significant increasing trends from 1995 to 2015, indicating that the revegetation has enhanced regional ET, confirming the results of previous study (Wang et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The trend reversal from decrease to increase in the region joining Shaanxi, Gansu, and Ningxia on the Loess Plateau was predominantly attributed to land development and ecological protection efforts (Liu et al, 2015). The extensive cultivation and the rapid development of husbandry industries caused vegetation degradation during the early years of the study period, whereas the implementation of the Grain to Green Program promoted vegetation growth and led to the trend reversal from decrease to increase (Xue et al, 2019). For the high mountains in Xinjiang, the weakly increasing precipitation and warming‐related snowmelt supplied plenty of water for boosting vegetation growth (He et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…The ensemble empirical mode decomposition (EEMD) method is capable of decomposing time‐series data into several frequency‐decreasing intrinsic mode functions ( IMF i , i = 1, 2…, n ) and a secular trend R n (Huang et al, 1998; Liu et al, 2016a). EEMD adds white noise to the raw series and then taking the ensemble mean to cancel out white noise (Pan et al, 2018; Wu & Huang, 2009; Xue, Zhang, He, & Shao, 2019). The decomposition steps can be described as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The Yuyang District is located at 37.81 • -38.92 • N, 108.94 • -110.41 • E (Figure 1), Shaanxi Province, China, and covers a total area of~7000 km 2 . This area is part of the ecologically fragile transition zone between the desert-grassland area and the Loess Plateau region [13,[49][50][51][52]. The region has a semi-arid continental monsoon climate, with an average annual temperature of 8.4 • C and an average annual precipitation of 402 mm that gradually decreases from the southeast to northwest.…”
Section: Study Areamentioning
confidence: 99%